2021
DOI: 10.1515/jbcpp-2020-0418
|View full text |Cite
|
Sign up to set email alerts
|

The effects of quercetin on nicotine-induced reward effects in mice

Abstract: Objectives Tobacco smoking remains the primary cause of preventable mortality and morbidity in the world. The complexity of the nicotine dependency process included the withdrawal effect that triggers recurrence being the main problem. Quercetin, known as an antioxidant, binds free radicals and modulates endogenous antioxidants through Nrf2 activations is expected as a potential agent to reduce the risk of nicotine dependence. This research aims to evaluate quercetin’s effects on reducing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Our results are in accordance with those of Singh et al, who reported that repeated administration of quercetin (25 and 50 mg/kg) for 9 days suppressed naloxone-precipitated morphine (10 mg/kg) withdrawal [31]. On the other hand, quercetin inhibited nicotinetriggered CPP reinstatement [42], alleviated METH-induced anxiety-like behavior in mice, attenuated the activation of astrocytes, and reduced the levels of IL-1beta and TNF-α, but not IL-6 [43]. In addition, quercetin (10, 30 and 100 mg/kg i.p.)…”
Section: Quercetin Abolished Heroin Dependence Acquisition and Inhibi...supporting
confidence: 93%
“…Our results are in accordance with those of Singh et al, who reported that repeated administration of quercetin (25 and 50 mg/kg) for 9 days suppressed naloxone-precipitated morphine (10 mg/kg) withdrawal [31]. On the other hand, quercetin inhibited nicotinetriggered CPP reinstatement [42], alleviated METH-induced anxiety-like behavior in mice, attenuated the activation of astrocytes, and reduced the levels of IL-1beta and TNF-α, but not IL-6 [43]. In addition, quercetin (10, 30 and 100 mg/kg i.p.)…”
Section: Quercetin Abolished Heroin Dependence Acquisition and Inhibi...supporting
confidence: 93%